Evaluation of safety and efficacy of inhaled ambroxol in hospitalized adult patients with mucopurulent sputum and expectoration difficulty - Zheng, Zeguang; Yang, Kai; Liu, Ni; Fu, Xiuhua; He, Huijie; Chen, Hong; Xu, Peijun; Wang, Jing; Liu, Maofeng; Tang, Yuling; Zhao, Fengzi; Xu, Shufeng; et al. (Frontiers in Medicine, 2023)
Background Ambroxol is a widely used mucoactive drug in sputum clearance of respiratory diseases taken orally and by injection. However, there is a paucity of evidence for inhaled ambroxol in sputum clearance. Methods This study performed a multicenter, randomized, double-blind, placebo-controlled, phase 3 trial at 19 centers in China. Hospitalized adult patients with mucopurulent sputum and expectoration difficulty were recruited. Patients were randomized by 1:1 to receive inhalation of either ambroxol hydrochloride solution 3 mL (22.5 mg) + 0.9% sodium chloride 3 mL or 0.9% sodium chloride 6 mL twice daily for 5 days, with an interval of more than 6 h. The primary efficacy endpoint was the absolute change in the sputum property score after treatment compared to the baseline in the intention-to-treat population. Results Between 10 April 2018 and 23 November 2020, 316 patients were recruited and assessed for eligibility, of whom 138 who received inhaled ambroxol and 134 who received a placebo were included. Patients who received inhaled ambroxol had a significantly greater decrease in the sputum property score compared with patients who received inhalation of placebo (difference: −0.29; 95% CI: −0.53 to −0.05; p = 0.0215). Compared with the placebo, inhaled ambroxol also significantly reduced more expectoration volume in 24 h (difference: −0.18; 95% CI: −0.34 to −0.03; p = 0.0166). There was no significant difference in the proportion of adverse events between the two groups, and no deaths were reported. Discussion In hospitalized adult patients with mucopurulent sputum and expectoration difficulty, inhaled ambroxol was safe and effective for sputum clearance compared with a placebo. Clinical trial registration [https://www.chictr.org.cn/showproj.html?proj=184677], Chinese Clinical Trial Registry [ChiCTR2200066348].